Evaluation of Antidepressant Activity of Tricholepis Angustifolia in Experimental Animal - Fuladi Nikhil,; Paithankar Vivek V,; Vyas Jugalkishor,; Wankhade Anjali, (Asian Journal of Pharmaceutical Research and Development, 2024)
Depression is increasingly recognized as a highly prevalent and chronic disorder. Long term use of the commonly prescribed antidepressants, like Benzodiazepines has been associated with adverse effects such as withdrawal effects and dependence. Herbal medications used in traditional medicinal systems are a potential avenue for developing newer drugs with desirable profiles. In Ayurveda, the roots of Tricholepis Angustifolia have been employed for treating various neurological diseases. The present study was undertaken to assess the antidepressant property seen on chronic administration of ethanolic extract of roots Tricholepis Angustifolia(EETA) in Swiss Albino Rats using the Elevated Plus Maze Test. 30 inbred adult male Swiss Albino rats were divided into 5 groups (n=6). The test groups received EETA in doses of 200mg/kg bw, 400 mg/kg bw and 600 mg/kg bw. Standard and control groups received Diazepam and normal saline, respectively. All drugs were administered orally once daily for 05 days. On the 05th day, 45 minutes post-administration, the exploratory and disinhibitory behaviour of the animals were evaluated for a 5 minute period each in the elevated plus maze. EETA in doses of 200mg/kg bw, 400 mg/kg bw significantly (p<0.05) increased the time spent in open arms, number of rears in open arms, as well as open and total arm entries when compared to control group. Chronic administration of EETA has displayed antidepressant property in rat subjected to the elevated plus maze paradigm. The present study indicated the potential for use of EETA as an adjuvant in the treatment of depression.